Application of CSM-CERES-Maize Model to Define a Sowing Window and Nitrogen Rates for Rainfed Maize in Semi-arid Environment - Rani, P. Leela (International Journal of Bio-resource and Stress Management, 2023)
Growing period or planting window concept is a useful approach in identifying suitable planting time to ensure crop success under rainfed conditions. CERES-Maize model was validated with experimental data collected during 2009 and 2010 to ensure its fitness in the region in order to simulate the growth and development of hybrid maize under semiarid environment of Hyderabad and to determine the impact of various sowing windows and N application rates on grain yield of maize crop. Validation of CERES-Maize model confirmed that the model can be used as a research tool in the variable agro-environments of Andhra Pradesh to suggest suitable sowing window and optimum nitrogen rate. Seasonal analysis tool of DSAAT model was used to optimize sowing date and nitrogen rate, using 30 years historical daily weather data from 1981 to 2010 for 154 different scenarios (treatment combinations; 14 sowing dates×11 nitrogen levels) starting from 01 June to 31 August at weekly interval and nitrogen levels ranging from zero (0) to 500 kg ha-1 at 50 kg incremental increase. The simulation scenarios showed that under rainfed conditions, 15 June sown crop predicted the highest average grain yield of 5449 kg ha-1 and it was on par up to 29 June sown crop. The median yield decreased consistently with each delay in time of sowing. Based on seasonal analysis the optimum sowing window for rainfed maize would be from 8 June to 29 June. The response to nitrogen was up to 150 kg N ha,-1 and there was no response to any added N beyond 150 kg N ha-1.